MEMBIDIK PENALARAN HAKIM DI BALIK SKOR "KOSONG-KOSONG" DALAM KASUS PRITA MULYASARI - Shidarta Shidarta (Jurnal Yudisial, 2011)
ABSTRACTThe case of Prita Mulyasari versus Omni International Hospital et al. is one of attractive legal problems happened in the last three years. In the context of private legal action, the Supreme Court had declared Prita was not guilty to spread her email because expressing somebody's feeling through personal and restricted communication media is not considered unlawful. On the other hand, any claim of malpractice should be proved by the claimant. According to the court's ruling, Prita failed to establish the evidences in order to support her statement. The court also relied on the assessment of malpractice to the Indonesian Medical Doctor Ethics Board. Such ways of thinking are the focuses of analysis in this article. The author believes there are some fallacies of legal reasoning occurred in this court decisio Keywords: legal reasoning, tort, malpractice, ethics ABSTRAKKasus Prita Mulyasari melawan Omni International Hospital dkk adalah sebuah perkara hukum yang menarik perhatian publik dalam kurun waktu tiga tahun terakhir. Dalam kasus perdata,MA menyatakan Prita tidak bersalah menyebarluaskan surat elektroniknya karena perbuatan mengungkapkan persaan seseorang melalui media komunikasi pribadi dan terbatas bukanlah perbuatan melawan hukum. Pada sisi lain, gugatan malpraktik yang diajukan Prita haruslah dibuktikan oleh si penggugat. Menurut majelis hakim kasasi, Prita gagal membuktikan gugatannya itu. Pengadilan juga mengandlkan penilaian malpraktik ini pada Majelis Kehormatan Dokter Indonesia. Artikel ini memfokuskan perhatiannya pada cara hakim bernalar atas kasus ini. Penulis menemukan sejumlah kesesatan penalaran dalam putusan ini. kata kunci: penalaran hukum, perbuatan melawan hukum, malpraktik, etika.